Analisis Perbandingan Titik Koordinat Google Maps Dan Alat GPS Profesional Di Kota Manado - Singal, Luciana; Rindengan, Yaulie D. Y. (Universitas Sam Ratulangi, 2021)
Abstract — GPS (Global Positioning System) is a system of navigation satellites in monitoring the position of the earth coordinates. The process of taking the location will obtain coordinates called waypoints (latitude and longitude on the map). Currently available on the android smartphone mapping application, namely Google Maps. One feature that many people find useful is its latitude and longitude GPS coordinate point information. Google Maps is designed to meet the needs of its users. Like looking for local businesses, looking at maps, getting directions. The professional GPS tool, Garmin Montana (680) is a GPS device that can view and manage maps, waypoints, routes and trails. The method used in this research is descriptive qualitative research which results from the research through visualization of tables and graphics. This study aims to compare the coordinates of Google Maps and Garmin Montana with the results of linear distance calculations and process the data using standard deviation. Through Google Maps observations, the calculation results obtained an average abscissa shift of 1.490272 m with a standard deviation obtained of 0.27216 m, while the results of the calculation of observations by GPS tools get a value of 1.49029 m with a standard deviation of 0.027212 m. Where the greater the results obtained from the standard deviation, the level of accuracy, the data results can be said to be inaccurate. Keywords — Coordinate point; Garmin Montana 680; Google Maps; GPS; GPS tools; Abstrak — GPS ( Global Positioning System) adalah sistem satelit navigasi dalam pemantauan posisi koordinat bumi.Saat ini telah tersedia pada smartphone android aplikasi pemetaan yaitu Google Maps. Salah satu fitur yang bermanfaat bagi banyak orang adalah informasi titik koordinat GPS lintang dan bujurnya. Google Maps dirancang untuk memenuhi kebutuhan dari penggunanya. Seperti mencari bisnis lokal, melihat peta, mendapat petunjuk tujuan. Alat GPS profesional yaitu Garmin Montana(680) merupakan alat perangkat GPS yang dapat melihat dan mengatur peta,titik acuan,rute dan jalur. Metode yang pada penelitian yaitu kualitatif yang bersifat deskriptif yang hasil dari penelitian melalui visualisasi tabel dan grafik. Penelitian ini bertujuan membandingkan titik koordinat Google Maps dan Alat GPS Profesional yaitu Garmin Montana dengan hasil perhitungan linier jarak dan mengolah data menggunakan standar deviasi. Melalui pengamatan Google Maps didapatkan hasil perhitungan rata-rata pergeseran absis sebesar 1,490272 m dengan standar deviasi yang diperoleh sebesar 0,27216 m, sedangkan hasil perhitungan pengamatan. Alat GPS mendapatkan nilai sebesar 1,49029 m dengan standar deviasi sebesar 0,027212 m. Dimana semakin besar hasil yang didapat dari standar deviasi maka tingkat akurasinya maka hasil data tersebut bisa dikatakan tidak akurat.Kata kunci — Titik koordinat; Garmin Montana 680; Google Maps; GPS; Alat GPS profesional.